2014
DOI: 10.1007/s00428-014-1614-6
|View full text |Cite
|
Sign up to set email alerts
|

Absence of caveolin-1 expression in carcinoma-associated fibroblasts of invasive micropapillary carcinoma of the breast predicts poor patient outcome

Abstract: Caveolin-1 (Cav-1) expression in stromal carcinoma-associated fibroblasts (CAFs) has been associated with tumor progression and clinical outcome. This study was undertaken to assess its prognostic significance in invasive micropapillary carcinoma of the breast (IMPC), a tumor with abundant stromal CAFs and a high tendency for nodal metastasis and poor outcome. Cav-1 expression was studied by immunohistochemistry in a group of 86 cases of IMPC along with a control group of 105 cases of invasive ductal carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The group also found that cytokines and membrane proteins, such as stromal cell-derived factor-1 and its receptor CXCR4, and caveolin-1 has a role in the metastases of IMPC. 45,53,54 Breast cancer cells with a CD44 þ /CD24 À/low phenotype have been proposed to have tumor-initiating properties, and this tumorigenic phenotype is considered a stem cell-like feature. 55 Li et al 51 demonstrated that the ratio of CD44 þ to CD24 À/low tumor cells was higher in IMPCs than it was in IDC-NOS, and the increased CD44 þ to CD24 À/low ratio was associated with more-frequent metastasis of IMPC and a worse prognosis.…”
Section: Mechanism Of Metastasismentioning
confidence: 99%
“…The group also found that cytokines and membrane proteins, such as stromal cell-derived factor-1 and its receptor CXCR4, and caveolin-1 has a role in the metastases of IMPC. 45,53,54 Breast cancer cells with a CD44 þ /CD24 À/low phenotype have been proposed to have tumor-initiating properties, and this tumorigenic phenotype is considered a stem cell-like feature. 55 Li et al 51 demonstrated that the ratio of CD44 þ to CD24 À/low tumor cells was higher in IMPCs than it was in IDC-NOS, and the increased CD44 þ to CD24 À/low ratio was associated with more-frequent metastasis of IMPC and a worse prognosis.…”
Section: Mechanism Of Metastasismentioning
confidence: 99%
“…Another study, which focused on the size of the primary tumors opposed to metastasis, reported that intradermal coinjection of nude mice with B16F10 melanoma cells and Cav1 KO neonatal dermal fibroblasts increased primary tumor growth when compared to coinjection of tumor cells with WT fibroblasts ( Capozza et al, 2012 ). While no known direct replications of the original study have been reported, several studies have assessed the role of stromal Cav1 expression in different types of tumors, with some studies reporting high Cav1 expression correlated with poor patient survival ( Linke et al, 2010 ; Goetz et al, 2011 ; Righi et al, 2014 ), and others reporting low Cav1 expression in the stroma negatively correlated with survival ( Simpkins et al, 2012 ; Ma et al, 2013 ; Zhao et al, 2013 ; Ren et al, 2014 ).…”
Section: Introductionmentioning
confidence: 98%
“…Several studies compared their cohort of IMPC patients to invasive ductal carcinoma (IDC) controls matched by disease stage and revealed a significantly higher incidence of lymph node metastasis in IMPC patients, particularly for early stage breast cancer [9][10][11][12]14,[23][24][25]28,31,32]. Yu [19-21] b Case series 68 68 NA Tressera et al [26] Case series 15 15 NA Middleton et al [22] Case series 14 14 NA Walsh and Bleiweiss [29] Case series 80 80 "Pure" (n =17), "partial" (n =63, range 5-95%) Wei et al [30] Case series 100 100 475% (n= 42), 50-75% (n=20), 25-50% (n =15), o25% (n=23) Varga et al [27] Case series 11 11 NA Li et al [18] Case series 40 40 "Pure" (n =9), "mixed" (n =31) Chen et al [14] Case series 100 100 NA Shi et al [25] Case series 188 188 "Pure" (n =27), "mixed" (n= 161) Kim et al [11] Cohort 250 38 450% (n= 17), o50% (n =21) Nassar et al [12] Cohort 1400 83 480% (n= 10), "minor proportion" (n =73) Kuroda et al [17] Cohort 671 27 "Some" De La Cruz et al [15] Cohort 1056 16 "Pure" (n =10), "mixed" (n= 6) Zekioglu et al [32] Cohort 2022 53 475% (n= 47), o75% (n =6) Pettinato et al [13] Cohort 1635 62 50-100% (n =40), 25-50% (n =12), o25% (n=10) Yu et al [31] Cohort 2753 72 470% (n= 72) Vingiani et al [28] Cohort 13,278 49 "Pure" (n =49) Paterakos et al [23] Cohort 1287 21 "Pure" (n =21) Gocke et al [10] Cohort 2718 103 "Pure" (n =20), "mixed" (n= 83) Ren et al [24] Cohort 5625 86 NA Chen et al [8,9] however no difference was seen on overall survival analysis.…”
Section: Discussionmentioning
confidence: 99%